The Effect Of Teamwork And Work Discipline On Employee Performance At PT. Trisula Ulung Mega Surya, Kecamatan Kabawetan, Kabupaten, Kepahiang - Dayu Dwi Pangestu; Taufik Bustami (PT. MEMIKATTA PUBLISHER INDONESIA, 2024)
The purpose of this study was to determine the effect of teamwork and work discipline on the performance of employees at PT. Trisula Ulung Mega Surya. This type of research is quantitative research. The sample in this study were 100 employees who worked at PT. Trisula Ulung Mega Surya. Data collection techniques in this study used observation and questionnaires. Data analysis techniques in this study were data validity tests, data reliability tests, data normality tests, correlation tests, and regression tests. The results of the research that has been done is that there is a significant relationship between teamwork and employee performance at PT. Trisula Ulung Mega Surya, by having a relationship in the strong category, there is a significant relationship between work discipline and employee performance at PT. Trisula Ulung Mega Surya, with a relationship in the moderate category. And there is a significant relationship between teamwork and work discipline with the performance of employees at PT. Trisula Ulung Mega Surya, by having a very strong relationship in the category.